Utility of Urine Cytology as per The Paris System in patients attending Birat Medical College - Kafle, Neeta; Sinha , Amrita; Sedhain , Sapana; Bhattarai , Soorya (Nepal Journal of Medical Sciences, 2025)
Introduction: Urine Cytology is a cheap, simple and non-invasive diagnostic tool to detect urothelial carcinoma. Previously there was no common standard and reproducible system to report urine cytology. The Paris system of reporting urinary cytology was conceived to produce uniformity in reporting Urinary cytology. We have been reporting urine cytology in our institution by conventional method and we intend to adopt this standard reporting in our laboratory. Thus this study was conducted to assess the utility of urine cytology reporting as per The Paris System of Reporting Urinary Cytopathology. Methods: This is a cross-sectional study conducted in the Department of Pathology, Birat Medical Teaching Hospital. Total enumeration sampling was done where all 57 voided as well as post instrumentation urine received over a period of 12 months was included in the study. Inadequate sample and patient not willing to take part in the study were excluded from the study. Cytological features were evaluated and classified according to the Paris system Histopathological features were evaluated and correlated wherever available. Results: The sensitivity, specificity, positive predictive value and negative predictive value for detecting high grade lesions were 88.9%, 100%, 100% and 94.4% respectively. Similarly sensitivity, specificity, positive predictive value and negative predictive value for detecting low grade lesions were 80%, 95.2%, 80% and 95.2% respectively. Conclusions: The standardized Paris system has high sensitivity, specificity, positive predictive value and negative predictive value in diagnosing urothelial malignancy especially High Grade Urothelial Carcinoma. Thus we recommend to implement this Paris system in our routine urine cytology reporting.